Cyanobacteria : cell isolation technique and establishment of clonal cultures - Mardhiah, Abdul Majid. (Universiti Malaysia Sarawak, (UNIMAS), 2006)
A study was carried out to identify and isolate selected cyanobacteria species, found to be predominant causing blooms on the water surface in freshwater environment. The water samples were collected from three different fish ponds in Indigenous Fisheries Research and Production Centre, Tarat Inland Fisheries Division, Serian. Three species were identified from the collected samples, namely Microcyslis sp.. Oscil/aloria sp. and Anabaena sp. These cyanobacteria were potentially cyanobacterial toxin producers. Cell isolation was carried out by streaking method procedure and consequently establishes the liquid culture of the small volume. The cultures were incubated in BO II and fl2 medium for 25° C with 7000 lux light intensity (12: 12, light: dark). Microcyslis sp. was successfully isolated and cultivated. However, the Oscil/moria sp. and Anabaena sp. clonal cultures were faced difficulties to establish. This study also found that different morphology namely unicellular, colonial and filamentous required different cell isolation protocol and medium composition. The best amount of initial number cell density to successfully clonal cultures the Microcyslis sp. was between 1.00 x 104 cells/ ml to 1.50 x 104 cells/ ml.